Driving Brand Growth in the Global FMCG Hydration Category: an Integrated Model of Ecosystem Strategy, Consumer Engagement, and IMC with Brand Experience as a Mediator - Budhi Heriyanto, Agustinus Yanuar; Antonius Bramantyo Indra Jaya (Universitas Mohammad Husni Thamrin, 2026)
The fast-moving consumer goods (FMCG) industry is experiencing rapid transformation driven by evolving consumer behavior, increasing health awareness, and growing demand for personalized and meaningful brand interactions. In this competitive environment, firms are shifting from product- and price-based competition toward integrated, relationship-oriented strategies aimed at creating sustainable brand growth. This study examines the effects of ecosystem-based marketing strategy, consumer engagement, and integrated marketing communication (IMC) on brand growth, with brand experience as a mediating variable in the FMCG industry. Data were collected from 100 respondents and analyzed using PLS-SEM with a Hierarchical Component Model (HCM). The results show that ecosystem strategy significantly affects consumer engagement (β = 0.72), brand experience (β = 0.45), and brand growth (β = 0.21). Consumer engagement influences brand experience (β = 0.40) and brand growth (β = 0.28), while brand experience strongly affects brand growth (β = 0.35). IMC also significantly impacts brand experience (β = 0.38) and brand growth (β = 0.22). The model demonstrates strong explanatory power (R² = 0.61–0.68). Mediation analysis confirms that consumer engagement and brand experience jointly mediate the relationship between marketing strategies and brand growth. These findings indicate that brand growth is driven by a multi-stage process involving engagement and experiential mechanisms.